Science, technology, and economic development : (Praeger Publishers, 1978)
This paper provides a view of science and technology policy as seen from the experience and perspective of the research program supported by the International Development Research Centre. First, the paper defines the subject area that is most relevant for developing countries. Then it charts the changing perspectives of developing-country researchers and policy makers as to the most important issues of concern over time. Subsequently, the paper discusses some important issues and conclusions that have been highlighted in recent research and draws out some of the critical issues raised by the papers in this special issue. Finally, the paper concludes with a few remarks on current knowledge and practice, gaps between the two, and recommends that the research results need to be embedded within formal teaching programs as a step to increase the utilization of knowledge.